(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
This article explores the development of modern Scottish literature within the British cultural space, focusing on the concept of sense of place as a key aesthetic and ideological category. Drawing on postcolonial and cultural-literary theory, the study examines how Scottish writers employ urban space, language variation, and historical memory to articulate national identity under conditions of cultural dominance. Particular attention is paid to the literary representation of Glasgow and Edinburgh in the works of Alasdair Gray and Ian Rankin, where the city functions not merely as a setting but as a symbolic and semantic construct. The article argues that modern Scottish prose constructs an alternative aesthetic system through the re-semanticization of local space and language, forming a hybrid cultural model characteristic of postcolonial literature.